Speech acts of Gandalf the grey in the Lord of the Rings: Fellowship of the ring - Wira Tunggul Segara Agus; Cicilia Arumsari (Universitas Sarjanawiyata Tamansiswa, 2022)
This research is aimed at describing the types of speech acts employed by Gandalf the Grey in a movie entitled The Lord of The Rings: Fellowship of the Ring and the reason behind each speech act uttered. This research applied a discourse analysis method using the movie transcript as the main source of data. The research reveals three findings. First, the locutionary acts employed by the protagonist, Gandalf the Grey, are declarative, interrogative, and imperative. The most used form by Gandalf the Grey is the declarative form, while the least used form is the Interrogative. Second, Gandalf the Grey employs four types of illocutionary acts. There are directive, representative, commissive, and expressive. He mostly employs the directive followed by the representative in the second place. Gandalf the Grey rarely use commisive and expressive form. Third, there are ten types of perlocutionary acts obtained as the effect of what Gandalf the Grey has uttered. There is a hearer who thinks of something, the hearer is doing something, the hearer knows something, the hearer is convinced, the hearer feels irritated, hearer feels frightened, the hearer is amused, the hearer is attracted, the hearer relieves tension, and hearer gives the answer. The first two of those types are the most dominant types. As a response to Gandalf the Grey’s statements and orders, the hearers are mostly required to think and then do something related to it.